2011
DOI: 10.3354/aei00025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the environment and culture depth on growth and mortality in juvenile Pacific oysters in the Strait of Georgia, British Columbia

Abstract: The effects of environmental variables, culture depth, and phytoplankton abundance and composition on juvenile Pacific oyster Crassostrea gigas growth and mortality were studied between June and October of 2008 at 4 sites in the Strait of Georgia, British Columbia, Canada. In addition, the effects of temperature-triggered depth manipulation on growth and mortality of oysters were examined in order to assess potential control measures for mitigating high summer mortalities associated with high temperature, harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Food content in the seawater can interact with temperature and influence the energy storage and their spawning event (Dridi, Romdhane & Elcafsi ). Seasonal growth rate depended on temperature, salinity, total suspended matter (TSM), organic matter (OM), inorganic matter (IM) and chlorophyll a (Fleury, Goyard, Mazurié, Claude, Bouget, Langlade & Le Coguic ; Cassis, Pearce & Maldonado ). Survivorship curves depends on physical factors such as temperature, salinity, desiccation, excessive deposition of silt and biological factors such as predators, parasites, pathogens and competitors for food and space (Tomaru, Kawabata & Nakano ; Lodeiros, Pico, Prieto, Narváez & Guerra ; Chávez‐Villalba, Hernández‐Ibarra, López‐Tapia & Mazón‐Suástegui ).…”
Section: Introductionmentioning
confidence: 99%
“…Food content in the seawater can interact with temperature and influence the energy storage and their spawning event (Dridi, Romdhane & Elcafsi ). Seasonal growth rate depended on temperature, salinity, total suspended matter (TSM), organic matter (OM), inorganic matter (IM) and chlorophyll a (Fleury, Goyard, Mazurié, Claude, Bouget, Langlade & Le Coguic ; Cassis, Pearce & Maldonado ). Survivorship curves depends on physical factors such as temperature, salinity, desiccation, excessive deposition of silt and biological factors such as predators, parasites, pathogens and competitors for food and space (Tomaru, Kawabata & Nakano ; Lodeiros, Pico, Prieto, Narváez & Guerra ; Chávez‐Villalba, Hernández‐Ibarra, López‐Tapia & Mazón‐Suástegui ).…”
Section: Introductionmentioning
confidence: 99%
“…It raises questions about the future of such monospecific culture systems facing new hazards. The recent degradation of natural conditions with increasing temperatures and ocean acidification has reduced the natural resilience of these coastal systems (Harvell et al 1999, Cassis et al 2011, Domeneghetti et al 2014, Ekstrom et al 2015. Ecosystems could deteriorate in the future because of increasing CO 2 and ocean acidification.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational responses (e.g., state aid, mutual funds, diversification strategies, private insurance, inventories, and savings) occur at both individual and collective levels (Grizel 1983, Le Bihan et al 2013, Lupo et al 2014. These responses also take the form of changes in practices and management rules such as limiting effort, reducing bivalve density, going off the coast, changing the culture height in the water column, triage of dead oysters, and building cages against predation (Smith et al 2000, Cassis et al 2011, Pernet et al 2011, Soletchnik et al 2011.…”
Section: Societal Responses To Mass Mortalities Of Bivalves Issuesmentioning
confidence: 99%
“…However contradictory findings were obtained in North Wales by King et al (2006) who found gonad development to be greater at high shore compared to low shore sites, though oysters showed little maturation and spawning. Experiments in British Columbia on the growth rate and mortality of oysters suspended at different depths within the water column (Cassis et al 2011) showed that these parameters were affected by depth, temperature, freshwater input, phytoplankton abundance and assemblage composition. On the west coast of Ireland differences in the condition of intertidal and subtidal oysters varied between sites and among months (R. Mag Aoidh, unpubl.data).…”
Section: Marine Planning and Husbandrymentioning
confidence: 99%